DEVELOPMENT AND ROLE OF EDUCATION: NORTH EAST INDIA - Tenzin Tsega (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The want and will to learn is observed throughout the past, which has transformed the history of mankind, from ground breaking inventions, that brought revolutionary changes facilitating and influencing our daily lives. The transition from a traditional system of education to the introduction of a formal system of education has further accelerated a progressive society in fields of science, social science, politics and many fields with inquisitive minds and critical thinkers, so much so that today education is looked upon as a requisite for a civilised society. Considering the difference in the experience of the introduction of a formal system of education worldwide, the impact of education thus differs, we have nations categorized as developed, developing, and underdeveloped based on its economic development, standard of living and industrialisation. Therefore, it becomes necessary to look into the development and role of education in international, national and regional levels which will help create an understanding and provide consciousness on the needs and changes. Hence this paper attempts to study the development and role of education in northeast India.